PSYCHOLOGICAL-EDUCATIONAL TECHNOLOGIES AS CONDITION OF ENHANCING OF EFFICIENCY OF PROFESSIONAL TRAINING OF BORDER GUARDS IN THE REPUBLIC OF INDIA - Bhinder, Nataliya (Educological discourse, 2018)
The article focuses on the analysis of psychological-educational technologies applied in the process of professional training of border guards in the Republic of India. The author outlines the purpose of the article – to describe three types of psychological-educational technologies in the process of professional training of border guards in the Republic of India and study the peculiarities of their implementation. Firstly, the notion of «psychological-educational technology» is defined as the use of combination of actions for improvement of educational process and systematic iterative process of application of various methods for enhancing of efficiency of professional training of future border guards; complicated and integrated process embracing all participants of training, their actions, ideas, devices and organization in order to analyze, develop, implement, evaluate and solve specific pedagogical tasks connected with formation of psychological readiness to perform service duties. On the basis of analysis of scientific literature we have revealed three psychological-educational technologies: yoga, traditional games and dance rhythmic therapy which have positive influence upon future specialists of border agencies. Psychological-educational technologies are used during lessons of physical training, hours of independent work, leisure time under supervision of ranking officers. Having found some unique psychological-educational technologies in the process of professional training used to develop psychological readiness to perform service duties in extreme situation, during conflicts of low intensity or in various geographical and climatic conditions, we have come to the conclusion that it is important to investigate the system of professional training of border guards in the Republic of India in details and reveal its strength with possible creative usage while training personnel of the State Border Guard Service of Ukraine.